2014
DOI: 10.1111/cpf.12215
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT measurements of small pulmonary vessels in chronic obstructive pulmonary disease: do they change on follow‐up scans?

Abstract: The aims of this study were to perform a longitudinal evaluation of the cross-sectional area (CSA) of small pulmonary vessels and the extent of emphysema measured on computed tomography (CT) scans of patients with chronic obstructive pulmonary disease (COPD), and to correlate the pulmonary vascular measurements with extent of emphysema. The institutional review board approved this retrospective study and waived the need for patients' informed consent. Seventy-four patients with COPD who underwent both initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
0
25
1
Order By: Relevance
“… 18 , 33 Saruya et al reported that there was a progressive increase in the extent of emphysema over time, but no significant decrease in small pulmonary vessels over the same time period. 20 They described that a decrease in the %CSA <5 may be associated with various improvements in the condition of the patients, such as smoking cessation, exacerbation risk, and pharmacotherapies, in comparison with emphysematous progression. Very recently, the morphological changes in small pulmonary vessels were reported to be associated independently with severe acute exacerbations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 33 Saruya et al reported that there was a progressive increase in the extent of emphysema over time, but no significant decrease in small pulmonary vessels over the same time period. 20 They described that a decrease in the %CSA <5 may be associated with various improvements in the condition of the patients, such as smoking cessation, exacerbation risk, and pharmacotherapies, in comparison with emphysematous progression. Very recently, the morphological changes in small pulmonary vessels were reported to be associated independently with severe acute exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on emphysema progression have been addressed, 16 18 but studies about the changes in airway disease 19 or vascular remodeling are rare. 20 The association between alveolar destruction, airway disease, and pulmonary vascular change also remains unknown. Moreover, the data on structural changes after exacerbation or smoking cessation in COPD patients are not established.…”
Section: Introductionmentioning
confidence: 99%
“…This decreased proportion of small pulmonary vessels has also been linked with pulmonary hypertension [116] and clinical outcomes [137] in COPD patients. Interestingly, longitudinal follow-up of CSA <5 mm 2 may indicate once more that vessel pruning precedes emphysema evolution [138]. Traditional explanations for pulmonary hypertension in COPD are emphysema destruction leading to loss of vasculature and hypoxemia-induced vasoconstriction.…”
Section: Pulmonary Vascularisationmentioning
confidence: 99%
“…The common threshold defining the lung parenchyma in emphysema was -900 to -960HU, and the most commonly used threshold was -950 HU [24]. In some study, different thresholds in the same sample had different correlations with airflow obstruction parameters in PFT [18,20,35,40].The broad range of published CCs between CT and PFT parameters were as follow: %LAA-950 and FEV 1 %pred, -0.66 to -0.09 [18,19]; %LAA-950 and FEV 1 /FVC, -0.75 to -0.09 [18,69]; %LAA 950 and FEV 1 %pred, -0.63 to -0.28 [19,59]; %LAA 950 and FEV 1 /FVC -0.66 to -0.54 [19,35];WA% and FEV 1 %pred, -0.713 to -0.044 [30,70];MLD and FEV 1 %pred, 0.18 to 0.85 [18,68]; MLD and FEV 1 /FVC, 0.21 to 0.89 [18,19];ATI and FEV 1 %pred, -0.725 to -0.29 [41,48]; WT and FEV 1 %pred, -0.68 to -0.13 [33,35]; WT and FEV 1 /FVC, -0.62 to -0.05 [33,35]; AI and FEV 1 %pred, 0.73 to 0.14 [28,33]; AI and FEV 1 /FVC, 0.32 to 0.07 [33,46];%LAA-950 and FEV 1 %pred by GE, -0.67 to -0.43 [26,60]; %LAA-950 and FEV 1 %pred by non-GE (such as Siemens, Toshiba, and Philips), -0.67 to -0.43 [39,47](Supplementary Table 3).…”
Section: Systematic Reviewmentioning
confidence: 99%